Sự suy giảm của màng nhựa acrylic nhũ tương primal AC-261 trong môi trường thời tiết nhân tạo - Vương, Nguyễn Thiên; Hùng, Đào Phi; Hiệp, Nguyễn Anh; Phúc, Mạc Văn; Thành, Trịnh Văn; Liên, Đinh Thị (Vietnam Journal of Chemistry, 2015)
The degradation of the Primal AC-261 water-based acrylic film (AC-261) in the artifical weathering environment has been studied by fourier-transform infrared (FTIR) and ultraviolet - visible (UV-Vis) spectroscopy, microscope and weight loss analysis. The IR and UV-Vis analysis showed that the level of C-H (alkanes) and C-O- (ester) stretchings decreased while O-H, C=O and C=C (alkene) stretchings increased in the artifical weathering testing process by a QUV weathering chamber equipped with UVB-313 fluorescent lamps and operated under wet-cycle conditions of 8 h UV irradiation at 60 °C, followed by 4 h of dark water condensation at 50 °C. After 96 cycles (1152 hours), the film surface had many black spots and weight loss of the film was 18 %.